Sosialisasi Konsumen Cerdas di Desa Tenajar, Kecamatan Kertasemaya, Kabupaten Indramayu - Riska Novitasari; Mohamad Sahid Rahman; Arif Darmawan; Despal; Sri Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Intelligent consumer socialization is a socialization activity that introduces how good and true consumer activities. Intelligent consumer socialization activities conducted in Tenajar Village, Kertasemaya Sub- district, Indramayu District. This activity was followed by the Housewives of the Tenajar village. Intelligent consumer socialization activities aimed at providing knowledge to housewives in Tenajar village about the intelligent consumer behaviour is to inspect the product before purchase, ensure the product according to SNI, buy according to the needs, The packaging label, as well as enforcing the rights and obligations as consumers. This activity also aims to educate the housewives into careful consumer behaviour, thorough in choosing, knowing the labels contained in the product packaging, knowing the rights of consumers, and knowing how to do the complain. The methods used are pre test, direct material delivery, direct practice, question and answer, and end with post test. Intelligent consumer socialization activities are able to improve the knowledge of the housewives regarding the rights and obligations as consumers. Hope ahead with the knowledge that belongs to the whole community Tenajar village able to apply the principles of intelligent consumers in daily life. Keywords: intelligent consumer, consumer behaviour, socialization.